Biocompatibility Assessment of Two Commercial Bone Xenografts by In Vitro and In Vivo Methods (2022)
Bone substitutes based on xenografts have been used for a long time in bone regeneration thanks to their inductive capacity for bone tissue regeneration. Some bone-based scaffolds have been modified by adding collagen and other proteins to improve their regenerative capacity and prevent migration and aggregation, especially particles. However, rejection of this graft has been reported due to protein residues caused by poor material preparation. We compared the in vitro and in vivo biological response of two commercial xenografts (InterOss®, F1 and InterOss® Collagen, F2) and a commercial porcine collagen membrane (InterCollagen® Guide, F3) as a rapid degradation control. Fourier Transform Infrared Spectroscopy (FT-IR) analysis evidenced the presence of hydroxyl, orthophosphate, and carbonate groups of the xenografts and amide groups of collagen. Thermogravimetric analysis (TGA) of the xenografts demonstrated their thermal stability and the presence of a few amounts of organic material. The study by differential scanning calorimetry showed the presence of endothermic peaks typical of the dehydration of the xenografts (F1 and F2) and for the collagen membrane (F3), the beginning of structural three-dimensional protein changes. Subsequently, in vitro biocompatibility tests were carried out for the materials with Artemia salina and MTT cell viability with HeLa cells, demonstrating the high biocompatibility of the materials. Finally, in vivo biocompatibility was studied by implanting xenografts in biomodels (Wistar rats) at different periods (30, 60, and 90 days). The F1 xenograft (InterOss) remained remarkably stable throughout the experiment (90 days). F2 (InterOss Collagen) presented a separation of its apatite and collagen components at 60 days and advanced resorption at 90 days of implantation. Finally, the collagen membrane (F3) presented faster resorption since, at 90 days, only some tiny fragments of the material were evident. All the in vivo and in vitro test results demonstrated the biocompatibility of the xenografts, demonstrating the potential of these materials for tissue engineering.